UGC Proposed Parameters for Institutional Excellence in IDP Framework - Dr. H. M. Naveen, (International Journal of Scientific Research in Science and Technology, 2024)
The UGC guidelines for institutional development plans for higher education institutions empowering the faculty is the critical pillar. Extending from purpose-informed recruitment processes to a culture that encourages continuous professional development. Faculty diversity is valued, nurturing talent, and offers pathways for career progression in line with and extending beyond global best practices. The eight enabler parameters are enumerated in the present context. Enablers of Governance, Financial, to Academic, Research & Intellectual Property, Networking & Collaboration, Human Resources, Supportive & Facilitative, Physical and Digital.
Keywords: UGC; Proposed Parameters; Institutional Excellence; IDP Framework